A Population Pharmacokinetic (Pk)- Pharmacodynamic (Pd) Analysis Of Peginesatide India Lysis Patients With Chronic Kidney Disease - Naik, Himanshu; Tsai, Max; Qiu, Ping; Vakilynejad, Majid (Kidney research and clinical practice, 2012)
Peginesatide is an erythropoiesis stimulating agent (ESA) being developed for the treatment of anemia due to chronic kidney disease in dialysis patients. The purpose of this analysis was to develop a population PK-PD model to characterize time-course of peginesatide plasma and hemoglobin (Hb) concentrations following administration of IV and SC peginesatide injections. This population PK–PD analysis included 4 phase 2 studies and 1 phase 3 study. Baseline subject demographics, laboratory values, and concomitant medications were evaluated as covariates in a stepwise manner. Models were evaluated for goodness-of-fit using diagnostic plots, predictability based on visual predictive check, and stability based on bootstrap analyses. The final PK model was a two compartment model with first-order absorption and saturable elimination. The final PD model was a precursor-dependent indirect response model with parameters accounting for the residual effect from the previous ESA doses (ESAD) and apparent change in disease condition (CF). The PD parameters shown below were estimated with good precision(relative standard error[RSE] ≤2%). Parameters Estimate RSE% EC50 (ng/mL) 401 2.0 Emax 0.542 1.6 Baseline Hb (g/dL) 11.5 0.40 MTT (mean transit time for red blood cells, h) 1640 0.49 MTP (mean transit time for progenitor cells, h) 462 1.1 ESA (residual effect from the previous ESA 0.153 0.66 CF (correction factor for disease condition) 0.000275 0.87 Total bilirubin, body mass index, age, alkaline phosphatase, ethnicity, and serum creatinine (for non-dialysis subjects) for PK and age and ESAD for PD were identified as statistically significant (p-value<0.005) covariates. None of these identified covariates were considered to be clinically relevant, based on their impact on simulated peginesatide exposure (<±30%) and Hb (<0.2 g/dL) levels.